Preparation, dynamic rheological behavior, crystallization, and mechanical properties of inorganic whiskers reinforced polylactic acid/hydroxyapatite nanocomposites. Issue 18 (18th January 2016) - Liu, Zhuo; Chen, Yinghong; Ding, Weiwei
ABSTRACT: The novel inorganic SiO2 –MgO–CaO whiskers (SMCWs) were incorporated into nano hydroxyapatite (HA) contained polylactic acid (PLA) system to prepare the reinforced PLA/HA/SMCWs nanocomposite. Maleic anhydride grafted PLA (PLA‐ g ‐MAH) was then used to modify the interface between filler and matrix. The morphology, rheological behavior, crystallization, and mechanical property of the prepared nanocomposites were systematically investigated using scanning electronic microscope, dynamic rheometer, differential scanning calorimeter, polarized light microscope, and mechanical test, respectively. The results showed that the introduced PLA‐ g ‐MAH obviously improves the filler dispersion and the filler–matrix interfacial compatibility. Interestingly, the incorporated whiskers obviously decrease the complex viscosity and hence could significantly improve the processability of system. However, the introduction of PLA‐ g ‐MAH increases the complex viscosity to a greater extent. In addition, the added whiskers were found to have complicated influences on the PLA crystallization. On one hand, the incorporated whiskers can enhance the melt crystallization capability of PLA macromolecular chains; on the other hand, the introduced whiskers also show the inhibitive effect on the nucleation of PLA polymer chains and the inhibition degree is related to the loading of whiskers. The combination of whiskers and PLA‐ g ‐MAH could remarkably improve the mechanical performance of PLA/HA nanocomposite. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43381. Abstract :